Ultrasound-Assisted Enhancement of Gel Properties in Hypomesus olidus Surimi - Yuan Fu; Guochuan Jiang; Xing Sun; Shuibing Yang; Jiahang Yu; Xuejun Liu; Liyan Wang; Shuangjie Zhu (Foods)
Surimi gel quality is crucial for seafood product texture and water retention, yet conventional processing often fails to maximize the potential of underutilized species like Hypomesus olidus. This study investigated the effects of ultrasonic power (100, 200, 400, 800 W) and time (5, 10, 15, and 20 min) on gel properties to establish optimal processing conditions. Results demonstrated that moderate ultrasonic treatment (200 W, 10 min) significantly enhanced gel quality, yielding a dense, uniform network with improved (p < 0.05) functionality: thr water-holding capacity increased by 35.88%, gel strength increased by 143.75%, and textural properties (hardness, cohesiveness, springiness, gumminess, chewiness) improved by 124.02%, 25%, 8.69%, 201.29%, 188.08% while maintaining color stability (1.59% whiteness increase). These improvements were attributed to optimized protein cross-linking and network formation. These findings provide a scientific basis for the ultrasonic processing of Hypomesus solidus surimi, offering practical parameters for industrial applications to enhance product quality efficiently. Future research should explore scaling effects and synergistic processing methods.